Navigating rice seedling cold resilience: QTL mapping in two inbred line populations and the search for genes - Schläppi, Michael R.; Jessel, Avery R.; Jackson, Aaron K.; Phan, Huy; Jia, Melissa H.; Edwards, Jeremy D.; Eizenga, Georgia C. (Frontiers in Plant Science, 2023)
Due to global climate change resulting in extreme temperature fluctuations, it becomes increasingly necessary to explore the natural genetic variation in model crops such as rice to facilitate breeding of climate resilient cultivars. To uncover genomic regions in rice involved in managing cold stress tolerance responses and to identify associated cold tolerance genes, two inbred line populations developed from crosses between cold tolerant and cold sensitive parents were used for quantitative trait locus (QTL) mapping of two traits: degree of membrane damage after one week of cold exposure quantified as percent electrolyte leakage (EL), and percent lowtemperature seedling survivability (LTSS) after one week of recovery growth. This revealed four EL QTL and 12 LTSS QTL, with all overlapping with larger QTL regions previously uncovered by genome-wide association study (GWAS) mapping approaches. Within the QTL regions, 25 cold tolerance candidate genes were identified based on genomic differences between the cold tolerant and cold sensitive parents. Of those genes, 20% coded for receptor-like kinases potentially involved in signal transduction of cold tolerance responses; 16% coded for transcription factors or factors potentially involved in regulating cold tolerance response effector genes; and 64% coded for protein chaperons or enzymes potentially serving as cold tolerance effector proteins. Most of the 25 genes were cold temperature regulated and had deleterious nucleotide variants in the cold sensitive parent, which might contribute to its cold sensitive phenotype.